The early solar system and its meteoritical witnesses - Jacquet, Emmanuel; Dullemond, Cornelis; Drążkowska, Joanna; Desch, Steven (Space science reviews, 2024)
Meteorites, and in particular primitive meteorites (chondrites), are irreplaceable probes of the solar protoplanetary disk. We review their essential properties and endeavour to place them in astrophysical context. The earliest solar system solids, refractory inclusions, may have formed over the innermost au of the disk and have been transported outward by its expansion or turbulent diffusion. The age spread of chondrite components may be reconciled with the tendency of drag-induced radial drift if they were captured in pressure maxima, which may account for the non-carbonaceous/carbonaceous meteorite isotopic dichotomy. The solid/gas ratio around unity witnessed by chondrules, if interpreted as nebular (non-impact) products, suggests efficient radial concentration and settling at such locations, conducive to planetesimal formation by the streaming instability. The cause of the pressure bumps, e.g. Jupiter or condensation lines, remains to be ascertained.